What are Teachers' Perceptions of Curriculum Changes - Yofita Gulo (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This journal research aims to see the implementation of teacher perceptions in curriculum development. This research uses quantitative research by collecting structured data through measurement instruments such as questionnaires. From the results of observations through questionnaires or systematic observations regarding this curriculum change, first, this curriculum change has an effect on learning styles, for example, if previously teachers only relied on books and blackboards when teaching, now it is all digital and of course this also makes it easier for teachers to teach and makes it easier for students to receive material from the teacher and can also influence learning models or methods. Meanwhile, changes to the curriculum can improve the quality of education. With this curriculum change, there are also challenges faced by schools, one of which is that teachers need to be prepared to utilize technology effectively in the learning process and also how to implement it. So, in conclusion, this curriculum change is indeed important but must be adjusted to the curriculum and current developments. In accordance with research that the author observed, schools currently prefer the Independent Curriculum. Keywords: curriculum, teacher, perception